Profile of Core Muscle Endurance, Body Mass Index and VO2MAX in New Residents of PSHT Batangsaren, Tulungagung Regency - Rahmad Amirul Hadi; Irwan Setiawan; Moh. Nur Kholis (CV. Nusantara Sporta, 2023)
This research is motivated by the observations and experiences of researchers that core muscle endurance, body mass index, and vo2max for new residents of the Batangsaren rayon are still lacking. As a result, coaches or residents are less than optimal in training their students to achieve achievements. The problems of this research are (1) What is the profile of the physical condition of new residents of Batangsaren Rayon Tulungagung Branch (2) What is the Body Mass Index of new residents of Batangsaren Rayon Tulungagung Branch (3) What is the core muscle endurance of new residents of Batangsaren Rayon Tulungagung Branch (4). What are the results VO2MAX, a new resident of the Batangsaren Rayon, Tulungagung Branch. This study uses a quantitative research approach that is descriptive in nature, the source of the data is obtained from physical condition tests taken by observers for new residents of the Batangsaren rayon, totaling 20 people. Data collection techniques used test techniques, measurement and analysis of data with percentage calculations. The conclusion of the results of this study is that the results of this study have very low core muscle endurance, totaling 9 people or 45%, body mass index (BMI) in the normal category, 16 people or 80% and more Vo2Max data, 17 people or 85%.